Optical multi-spark ammonia combustion engine: numerical analysis and validation - Menaca, Rafael; Silva, Mickael; Uddeen, Kalim; Almatrafi, Fahad; Tang, Qinglong; Turner, James W. G.; Im, Hong G. (Frontiers in Mechanical Engineering, 2025)
Ammonia (NH3) stands out as a promising candidate for fueling internal combustion engines, owing to its high hydrogen content and well-established production and transport infrastructure. Nevertheless, its inherently low flame speed and reactivity pose a significant challenge to achieving rapid and complete combustion. One potential solution is the use of multi-spark ignition, wherein multiple spark plugs distribute ignition sites throughout the combustion chamber, thereby accelerating flame propagation across the entire charge. In this study, a three-dimensional 3D-CFD model of multi-spark, spark-ignited NH3 internal combustion engine is developed and validated using optical engine experiments. The optical data provide critical insights into early flame kernel development, guiding refinements to two combustion submodels (SAGE and G-equation). Results underscore the importance of sufficiently refined mesh resolution—particularly near the spark plugs—and the incorporation of detailed spark plug geometries to accurately capture the early stages of ignition in low-reactivity fuels such as NH3. Overall, the close qualitative agreement between measured flame luminosity and simulated flame evolution demonstrates the robustness of the proposed CFD framework.